A first course in real analysis - Oon, Shea Ming (University of Malaya Press, 2017)
This book is designed for students who have a basic background in calculus and who wish to learn real analysis by themselves. It starts with a recall in set theory and mapping, before give a topological description of the real line. Real sequences and real series are studied in length, so as the concept of functions of a real variable. We end the study in asymptotic series for regular functions.